2008
DOI: 10.12693/aphyspola.113.291
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Lattice Defects on the Ground-State Properties of the Falicov-Kimball Model in Two Dimensions

Abstract: The influence of lattice defects (vacancies) on the ground-state properties of the spinless Falicov-Kimball model is studied by a well-controlled numerical method in two dimensions. It is shown that in the presence of vacancies (distributed randomly) the ground states of the Falicov-Kimball model are phase separated for small f -electron concentrations n f and exhibit the long-range order for n f near the half-filled band case n f = 1/2. In addition, the dependence of average f -orbital occupancy on the concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 5 publications
1
0
0
Order By: Relevance
“…2) shows that the IV state of Sm ions is maintained in Sm 1−x B 6 samples up to 20 % of concentration x of vacancies and the valence increases with increasing x. These results are in good qualitative agreement with susceptibility and Xray measurements [4,7] and exact numerical calculation of the spinless FKM in two dimensions [10]. This theoretical study of Sm 1−x B 6 has shown that the valence transition of Sm ions is maintained up to 25% of vacancy concentration x and that the average f -orbital occupancy, n f = 3 − v, decreases with x.…”
Section: Resultssupporting
confidence: 75%
“…2) shows that the IV state of Sm ions is maintained in Sm 1−x B 6 samples up to 20 % of concentration x of vacancies and the valence increases with increasing x. These results are in good qualitative agreement with susceptibility and Xray measurements [4,7] and exact numerical calculation of the spinless FKM in two dimensions [10]. This theoretical study of Sm 1−x B 6 has shown that the valence transition of Sm ions is maintained up to 25% of vacancy concentration x and that the average f -orbital occupancy, n f = 3 − v, decreases with x.…”
Section: Resultssupporting
confidence: 75%